Sympathetic and Vagal Nerve Activity in COPD: Pathophysiology, Presumed Determinants and Underappreciated Therapeutic Potential - Spiesshoefer, Jens; Regmi, Binaya; Ottaviani, Matteo Maria; Kahles, Florian; Giannoni, Alberto; Borrelli, Chiara; Passino, Claudio; Macefield, Vaughan; Dreher, Michael (Frontiers in Physiology, 2022)
This article explains the comprehensive state of the art assessment of sympathetic (SNA) and vagal nerve activity recordings in humans and highlights the precise mechanisms mediating increased SNA and its corresponding presumed clinical determinants and therapeutic potential in the context of chronic obstructive pulmonary disease (COPD). It is known that patients with COPD exhibit increased muscle sympathetic nerve activity (MSNA), as measured directly using intraneural microelectrodes – the gold standard for evaluation of sympathetic outflow. However, the underlying physiological mechanisms responsible for the sympathoexcitation in COPD and its clinical relevance are less well understood. This may be related the absence of a systematic approach to measure the increase in sympathetic activity and the lack of a comprehensive approach to assess the underlying mechanisms by which MSNA increases. Invasive assessment of muscle SNA to the point of single unit recordings with analysis of single postganglionic sympathetic firing, and hence SNA drive to the peripheral vasculature, is the gold standard for quantification of SNA in humans but is only available in a few centres worldwide because it is costly, time consuming and requires a high level of training. The point is made that although MSNA is undoubtedly increased in COPD (probably independently from concomitant cardiovascular disease), studies designed to determine clinical improvements during specific treatment will only be successful if they include adequate patient selection and translational state of the art assessment of SNA. This would ideally include intraneural recordings of MSNA and – as a future perspective – vagal nerve activity.